Caribbean Report 29-01-1998 - The British Broadcasting Corporation; Greaves, Keith Stone (anchor); Rousseau, Pat (interviewee); Hendriks, Jackie (interviewee); Roberts, Andy (interviewee); Crosskill, Simon (interviewee); Perez, Ninoska (interviewee); Da Silva, Phillip (interviewee) (The British Broadcasting Corporation, 1998)
In cricket, the match between England and the West Indies has been abandoned as the umpires decided that the pitch is unfit and dangerous to the players. President of the West Indies Cricket Board, Pat Rousseau explains the decision and its consequences. The Jamaica Cricket Board (JCB) President Jackie Hendriks comments on what went wrong with the preparation. Jamaicans express their disappointment and disgust about this cricketing fiasco and English supporters who traveled across the sea are even more perturbed. Sports commentator Simon Crosskill comments on the unfortunate situation and places the blame solely on the JCB. The Cuban American National Foundation (CANF), a hard-lined Cuban exile group, is defending its involvement in a plan to sent food aid to Cuba. CANF spokeswoman Ninoska Perez comments on if this move represented a significant softening of the group's position. With a major ice meltdown in the Antarctic, Phillip Da Silva talks about the real and immediate threat posed to Guyana, given that it lies below sea level. The Trinidad and Tobago government states it will discuss with Britain its intention to begin a phased pull-out from the traditional appeals to the Privy Council. 1. Headlines with Keith Stone Greaves (00:00-00:27) 2. A dangerous pitch in Jamaica causes the abandonment of the West Indies and England test match (00:28-05:57) 3. Simon Crosskill, sport commentator comments on this embrassment and the worst moment in Jamaican cricket (05:58-08:44) 4. Cuban American National Foundation, a hard-lined Cuban exile group, defends its involvement in a plan to send food to Cuba (08:45-11:08) 5. A major ice meltdown in the Antarctic could pose problems for the region especially Guyana, which lies below sea level (11:09-11:44) 6. The Trinidad and Tobago government plans to discuss with Britain its intention to begin a phased pull-out from the appeals to the Privy Council (11:45-12:16) 7. Recap of top stories (12:17-12:45)